Menengok Kembali Budaya Dan Masyarakat Megalitik Bondowoso - Muhammad Hidayat (Balai Arkeologi Yogyakarta, 2007)
There are quite a lot of megalithic cultural heritage in the eastern part of East Java, such as in the Jember, Bondowoso, Situbondo, and Banyuwangi areas. From several studies so far, it is known that the relics in the Bondowoso area are very dense in distribution, and the variety of cultural products is the greatest. Therefore it is not wrong to say that in the eastern region of East Java it is a megalithic kingdom with its capital in Bondowoso. Especially for the megalithic relics in Bondowoso, research has often been carried out. However, the studies that have been carried out cannot completely answer the problems regarding these legacies. New academic problems continue to emerge and require new information / data to answer them. Likewise, the emergence / discovery of new data that demands an explanation. · Among the problems that have not been answered satisfactorily until now are the people who support megalithic culture and the period of its development.